The net acid extruders NHE1, NBCn1 and MCT4 promote mammary tumor growth through distinct but overlapping mechanisms. Issue 12 (7th February 2018) - Andersen, Anne Poder; Samsøe‐Petersen, Jacob; Oernbo, Eva Kjer; Boedtkjer, Ebbe; Moreira, José M.A.; Kveiborg, Marie; Pedersen, Stine Falsig
Abstract : High metabolic and proliferative rates in cancer cells lead to production of large amounts of H + and CO2, and as a result, net acid extruding transporters are essential for the function and survival of cancer cells. We assessed protein expression of the Na + /H + exchanger NHE1, the Na + ‐ HCO 3 − cotransporter NBCn1, and the lactate‐H + cotransporters MCT1 and −4 by immunohistochemical analysis of a large cohort of breast cancer samples. We found robust expression of these transporters in 20, 10, 4 and 11% of samples, respectively. NHE1 and NBCn1 expression both correlated positively with progesterone receptor status, NHE1 correlated negatively and NBCn1 positively with HER2 status, whereas MCT4 expression correlated with lymph node status. Stable shRNA‐mediated knockdown (KD) of either NHE1 or NBCn1 in the MDA‐MB‐231 triple‐negative breast cancer (TNBC) cell line significantly reduced steady‐state intracellular pH (pHi ) and capacity for pHi recovery after an acid load. Importantly, KD of any of the three transporters reduced in vivo primary tumor growth of MDA‐MB‐231 xenografts. However, whereas KD of NBCn1 or MCT4 increased tumor‐free survival and decreased in vitro proliferation rate and colony growth in soft agar, KD of NHE1 did not have these effects. Moreover, only MCT4 KD reduced Akt kinase activity, PARP and CD147 expression and cell motility. This work reveals that different types of net acid extruding transporters, NHE1, NBCn1 and MCT4, are frequently expressed in patient mammary tumor tissue and demonstrates for the first time that they promote growth of TNBC human mammary tumors in vivo via distinct but overlapping mechanisms. Abstract : What's new? Net acid extruding transporters are critical to the survival of cancer cells, which have high metabolic rates and produce excess acid and lactate. Here, three net acid extruding transporters, NHE1, NBCn1, and MCT4, were found to be expressed in human mammary tumor tissue. Their expression varied according to hormone receptor status. In mice, additional variations were identified following transporter knockdown. NBCn1 or MCT4 loss led to reduced MDA‐MB‐231 breast tumor cell proliferation and anchorage‐independent colony formation, while only MCT4 knockdown decreased cell migration and invasion. The findings offer new insight into the relevance of net acid extruding transporters in breast cancer.